2005
DOI: 10.1002/app.21282
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of cotton cellulose in the presence of serine and glycine. I. Physical properties and reaction kinetics

Abstract: Serine and glycine were used to combine with dimethyloldihydroxyethyleneurea (DMDHEU) as crosslinking agents to study the physical properties of the crosslinked fabrics and the reaction kinetics, and find that the bound nitrogen is in the series of DMDHEU Ͼ Ͼ DMD-HEU-serine Ͼ DMDHEU-glycine at the same resin concentration. The results also show that the wet crease recovery angle (WCRA) value of the treated fabrics for the three crosslinking agent systems is in the series of DMDHEUserine Ͼ DMDHEU-glycine Ͼ DMDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…28,29 This will provide an additional N-CH 2 OH group, which can hydrolyze, thus resulting in a slow formaldehyde release (equation (7)). It was reported that the methylated DMDHEU is more resistant to both acid and alkaline hydrolysis than those from DMDHEU.…”
Section: Results and Discussion Formaldehyde Release Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 This will provide an additional N-CH 2 OH group, which can hydrolyze, thus resulting in a slow formaldehyde release (equation (7)). It was reported that the methylated DMDHEU is more resistant to both acid and alkaline hydrolysis than those from DMDHEU.…”
Section: Results and Discussion Formaldehyde Release Behaviormentioning
confidence: 99%
“…The fourth source is the formaldehyde released from the breaking of the crosslinks between DMDHEU and cellulose molecules, which was revealed by the gradual disappearing of ether group (1108 cm À1 ) as well as the formations of absorbing bands of -CH 2 OH (1027 cm À1 and 1077 cm À1 ) for DMDHEU and absorption peak of -OH for cotton fiber in their IR spectra. 28,29 This will provide an additional N-CH 2 OH group, which can hydrolyze, thus resulting in a slow formaldehyde release (equation ( 7)). It was reported that the methylated DMDHEU is more resistant to both acid and alkaline hydrolysis than those from DMDHEU.…”
Section: Formaldehyde Release Behaviormentioning
confidence: 99%
“…Yao et al have investigated crosslinking of cotton cellulose in the presence of serine, glycine, and dimethyloldihydroxyethyleneurea and the physical properties of the crosslinked fabrics. 35 Remadevi et al described glycine-treated cotton fibers at different pH values and studied their tensile, physical, and microstructure properties. 36 However, hydrogel preparation with crosslinking of microcrystalline cellulose by glycine has not been at the primary focus of any research groups to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al . have investigated crosslinking of cotton cellulose in the presence of serine, glycine, and dimethyloldihydroxyethyleneurea and the physical properties of the crosslinked fabrics . Remadevi et al .…”
Section: Introductionmentioning
confidence: 99%
“…studies [3,7] pointed out that the carboxylic acid of tartaric acid could interact with aluminum ion to release hydrogen ions to improve the catalytic effect, the crease recovery angles and the reaction rate constants. Our previous studies [8,9] showed that the physical properties of the treated fabrics with DMDHEU/alpha-amino acids were changed with the kinds of alpha-amino acids used.…”
mentioning
confidence: 99%